2014
DOI: 10.1080/09540121.2014.978730
|View full text |Cite
|
Sign up to set email alerts
|

Successes and gaps in uptake of regular, voluntary HIV testing for hidden street- and off-street sex workers in Vancouver, Canada

Abstract: Despite evidence globally of the heavy HIV burden among sex workers (SWs), as well as other poor health outcomes, including violence, SWs are often excluded from accessing voluntary, confidential and non-coercive health services, including HIV prevention, treatment, care and support. This study therefore assessed the prevalence and associations with regular HIV testing among street- and off-street sex workers (SWs) in Vancouver, Canada. Cross-sectional baseline data were used from a longitudinal cohort known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…The lowest rate was reported in a study conducted in India (7.9%, N = 6648) [18]. Ten studies examined recent testing [25, 27–29, 3540], which varied extensively from 76.1% in Canada (N = 435) [25] to 22% in China (N = 970) [38]. Six studies addressed willingness to test [1820, 28, 41, 42], and this ranged from 88% (N = 17) in China [41] to 73.2% in India (N = 6648) [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest rate was reported in a study conducted in India (7.9%, N = 6648) [18]. Ten studies examined recent testing [25, 27–29, 3540], which varied extensively from 76.1% in Canada (N = 435) [25] to 22% in China (N = 970) [38]. Six studies addressed willingness to test [1820, 28, 41, 42], and this ranged from 88% (N = 17) in China [41] to 73.2% in India (N = 6648) [18].…”
Section: Resultsmentioning
confidence: 99%
“…In Uzbekistan, FSWs who started sex work before the age of 18 were less likely to test [32], and in Canada older age of sex work initiation was positively associated with recent testing [25]. FSWs who engaged in sex work for a longer time had a higher uptake of testing [18, 20, 33, 45] and willingness to test [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bauer, 2012 29 Deering, 2012 31 Ghai, 2008 38 Gray, 2008 32 Mairs, 2010 37 Peterman, 2008 36 Raffa, 2010 30 Schwandt, 2011 34 Vibert, 2010 33 Wagner Non-probability sampling (not specified) Non-probability sampling Non-probability (venue-based and snowball) Non-probability sampling Non-probability sampling Non-probability sampling (venue-based, word-of mouth) Non-probability sampling Non-probability sampling (venue-based) Non-probability sampling limitations and gaps were uncovered, including a lack of research on certain specific populations and a lack of information on testing frequency and recent testing. Most studies relied on self-reported health behaviour information which is subject to social desirability response bias.…”
Section: Other Specific Populationsmentioning
confidence: 99%
“…The percentage of people ever tested from this category ranged from 10.4%-75.0%, with the lowest rate among young sexually active students (10.4%) and the highest rate among individuals from HIV-endemic countries (75.0%). [29][30][31][32][33][34][35][36][37][38] No information was provided on regular testing. Recent testing in the previous year was only reported in two studies.…”
Section: Other Specific Populationsmentioning
confidence: 99%